Implementing an Integrated Management System (IMS) : the Strategic Approach. - Field, Alan (IT Governance Ltd, 2019)
Understand how to implement an IMS (integrated management system) and how it can benefit your organisation An IMS incorporates all of an organisation's processes and systems so that they are working under - and towards - one set of policies and objectives. Your strategic guide to implementing an IMS - get the help and guidance you need!